Exploring Language Development in Early Childhood: A Linguistic Perspective - Erna Januairini (Yayasan Insan Cipta Medan, 2026)
This study aims to investigate the development of English vocabulary and communication skills in young children within early childhood education settings. The increasing importance of English as a global language has encouraged its introduction at an early age; however, young learners require appropriate strategies that suit their developmental characteristics. This study focuses on how children acquire basic vocabulary and develop simple communication abilities through classroom interactions and learning activities. This research employed a qualitative descriptive approach with a case study design conducted in an early childhood education institution in Indonesia. The participants consisted of children aged 4–6 years and an English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using thematic analysis, including data reduction, coding, categorization, and interpretation. To ensure the trustworthiness of the findings, triangulation and member checking techniques were applied. The findings indicate that children’s vocabulary and communication skills develop gradually through interactive and engaging activities such as songs, games, and storytelling. These activities help children improve their vocabulary, pronunciation, and ability to use simple English expressions. The teacher plays a significant role in facilitating learning through modeling, repetition, and scaffolding. However, limited exposure to English outside the classroom and differences in individual abilities were identified as challenges affecting language development.